Novel and recurrent genetic variants of VHL, SDHB, and RET genes in Chinese pheochromocytoma and paraganglioma patients - Li, Chong; Li, Jingyi; Han, Chao; Wang, Ting; Zhang, Lixia; Wang, Zhifang; Wang, Tingting; Xu, Lijun; Qi, Guangzhao; Qin, Guijun; Li, Xialian; Zheng, Lili (Frontiers in Genetics, 2023)
Background: Pheochromocytoma and paraganglioma (PPGL) are rare neuroendocrine tumors arising from chromaffin cells in the adrenal medulla and extra-adrenal ganglia, respectively. The study was aimed to investigate the clinical and genetic characteristics of 22 individuals from six families. Methods: The medical records of six PPGL probands who presented to our hospital between 2016 and 2021 were retrospectively studied. DNA isolated from the probands was analyzed using whole exome sequencing. The identified genetic variants were confirmed by Sanger sequencing and undergone bioinformatic analysis. Results: Six different genetic variants in the six probands were identified, respectively, of which three were novel. A novel von Hippel-Lindau (VHL) variant, c.602T>C (p.L201P), in exon 3 was found. Two novel genetic variants in SDHB (succinate dehydrogenases subunit B), c.423+1 G>T and c.662A>G (p.D221G), were identified. Two recurrent genetic variants of VHL, c.C284G (p.P95R) and c.558_560AGAdel (p.186Edel), and one in RET (ret proto- oncogene), c.1901G>A (p.C634Y), were also found. The ClinVar accession number for the present variants are SCV002028348, and SCV002028352 to SCV002028361. Conclusions: Genetic variants in VHL, SDHB and RET were identified in Chinese PPGL patients, which contributed to the knowledge of the genetic etiology and clinical outcome of these tumors.